SURGICAL TREATMENT OF SQUAMOUS CELL CARCINOMA IN A MALE CROSSBREED DOG - Ni Ketut Vonny Vonny; I Gusti Agung Gde Putra Pemayun; I Putu Krisna Ardhia Pradnyandika (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Squamous cell carcinoma is a non-melanoma malignant tumor originating from suprabasal epidermal keratinocyte cells. This tumor often occurs in elderly dogs in tropical countries due to ultraviolet radiation, viral infections, trauma, and immune status. The purpose of this article is to find out how to diagnose and treat squamous cell carcinoma cases in dogs. The case animal is a mixed breed dog, male, 10 years old, and weighs 21 kg. Clinical signs showed a lump with a solid consistency in the lateral left abdomen since 2 years. Based on the results of histopathological examination, the case dog was diagnosed with squamous cell carcinoma with a dubious prognosis. Treatment was carried out through surgical excision of tumor tissue, using general anesthesia with a combination of xylazine and ketamine with a total dose of xylazine 1.9 mg/kg BW and ketamine 9.5 mg/kg BW intravenously. Postoperatively, the dog was given cefotaxime antibiotic at a dose of 20 mg/kg BW intravenously (q12h) for 3 days and continued with oral cefixime antibiotic at a dose of 10 mg/kg BW (q12h) for 6 days. The dog was also given oral analgesic mefenamic acid at a dose of 10 mg/kg BW (q12h) for the first 3 days and continued with oral anti-inflammatory methylprednisolone at a dose of 0.4 mg/kg BW (q12h) for 6 days due to inflammation. On the 12th day, the surgical wound had healed as indicated by the skin had fused, was not swollen, the wound was dry, and the dog was actively moving. Further studies are needed on squamous cell carcinoma in dogs, and consideration should also be given to radiotherapy and/or chemotherapy to obtain better results.